Sustainable Design in Building and Urban Environment - Aram, Farshid (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The sustainable design approach in construction aims to minimize negative effects on the environment and the well-being of individuals in buildings and urban areas. It seeks to enhance the performance of buildings and urban spaces. The fundamental goals of sustainability include reducing the consumption of non-renewable resources, minimizing waste, and creating healthy and productive environments. Sustainable design principles encompass various aspects such as optimizing site potential, minimizing non-renewable energy consumption, using environmentally preferable products, conserving water, protecting and enhancing green resources, improving indoor and outdoor environmental quality, and optimizing operational and maintenance practices. By incorporating sustainable design principles, decisions made throughout the design process can effectively reduce adverse impacts on the environment and human health, while still considering economic considerations. This integrated and holistic approach encourages compromise and tradeoffs, positively influencing all stages of an urban environment's life cycle, including design, construction, operation, and decommissioning. This Special Issue, "Sustainable Design in Building and Urban Environment", introduces different methods regarding sustainable design in the field of civil engineering, architecture, and urban planning, from new techniques using computer simulation and artificial intelligence to studies of the traditional methods at historical sites.